UNDERSTANDING THE SPEECH CODES OF TOLERANCE IN CONSERVATIVE COMMUNITY - Aldana, Dava; Dwiningtyas Sulistyani, Hapsari; Qurrota Ayun, Primada (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
This interpretive qualitative research has aim to understand the speech code and logic of tolerance in conservative community. Based on the Ethnography of Communication, data is collected through WhatsApp groupchat and interview which later analysed with The Speech Code Theory (Gerry Philipsen) that resulting codes of tolerance that then elaborated using Social Identity Theory (Tajfel&Turner) in generating codes. The result of this research is: first, Code of Honor and Dignity. This code creates logic of Victim Perspective, namely the feeling of the ingroup as victims of getting pitted against each other by the outgroup which is based on the concept of Aqidah and Morals that the ingroup believed in. Second, the dominant code referring to Code of Outgroup namely act of excluding outgroup due to differences of perspective from each religion. This code also arises in fellow Muslim that has different ways in interpreting Islam. The logic appears due to protecting fellow Muslim from influence of the non-Muslim where later represent the existence of stratification among Muslim. Third, Phrases for Moral Judgments and codes of Prejudice emerging logic of moral and prejudice. This logic refers to direct judgments for outgroup based on moral superiority feeling of ingroup with the purpose of revealing the true face of Islam based on Quran and Hadist, where later arises group identity as the true believer of Islam. Those identity arises due to the urge of improving the face of Islam that perceived as old fashioned, radical, or even terrorist. However, code of non-verbal also arises in the chatgroup as a complimentary during conversation.